Muru’ah as a Mediator of Product Innovation among Local Snack MSMEs - Sitti Nurlinda; Syaparuddin Razak; Jumarni Jumarni (Universitas Islam Negeri Sumatera Utara, 2026)
This study examines the mediating role of muru'ah in the relationship between social networks, trust, external collaboration, and product innovation among local snack MSMEs in Bone Regency. Grounded in Social Capital Theory and Open Innovation Theory, the study employs a quantitative explanatory approach and analyzes data from 153 entrepreneurs using PLS-SEM. The results show that social networks and trust positively influence external collaboration, while social networks, trust, external collaboration, and muru'ah significantly contribute to product innovation. The findings further indicate that muru'ah plays a significant mediating role in linking social capital dimensions and product innovation. These findings highlight the importance of integrating ethical values and relational resources to strengthen innovation outcomes among MSMEs. The study contributes to the literature by extending the application of Islamic ethical values within innovation and entrepreneurship research